Combinatory lung tumor inhibition by myo-inositol and iloprost/rapamycin: association with immunomodulation. (11th February 2022) - Kassie, Fekadu; Bagherpoor, Alireza Jian; Kovacs, Katalin; Seelig, Davis
Abstract: Although both preclinical and clinical studies have suggested that myo-inositol (MI) may be a safe and effective lung cancer chemopreventive agent, its efficacy is moderate. To test whether the chemopreventive agents iloprost (IL) or rapamycin enhance the lung tumor inhibitory effects of MI, A/J mice were treated with the tobacco smoke carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and, beginning one week after the end of NNK treatment, given MI, IL, rapamycin, MI + IL or MI + rapamycin for 17 weeks. Analyses of the number and size of tumors on the surface of the lung have indicated that MI, IL, rapamycin, MI + IL and MI + rapamycin reduced the multiplicity of NNK-induced lung tumors by 41, 34, 46, 79 and 67%, respectively, and larger tumors (lung tumors with a diameter of 1–2 or >2 mm) were absent in the MI + IL and MI + rapamycin groups. These results clearly indicated that MI + IL and MI + rapamycin are more effective than MI alone in inhibiting the formation and growth of lung tumors. Assessment of the immunomodulatory effects of the drugs showed that whereas MI + rapamycin and MI + IL increased the infiltration of lung tumors by CD4 + and CD8 + T cells, MI + rapamycin reduced the expression of the immune checkpoint protein programmed-death ligand-1 (PD-L1). Moreover, all treatments, except IL, increased apoptosis, whereas cell proliferation was markedly suppressed in all treated groups. In summary, these results suggest that IL and rapamycin could enhance the efficacy of MI in lung cancer chemoprevention trials. Abstract : We show that the chemopreventive agents iloprost and rapamycin potentiate the inhibitory effects of myo-inositol on early stage lung tumorigenesis, at least in part, by increasing the abundance of CD4 + and CD8 + tumor-infiltrating lymphocytes. Graphical Abstract: